The Invisible Big Waves: How Indonesia Combat with Radicalism and Terrorism in Global Perspective - Ridwan Arifin; Ali Masyhar; Btari Amira (Jurnal Hikmatuna, 2020)
This paper is qualitative research, discusses and examines how government combating radicalism and terrorism in relation with global and international perspective. From these incidents, various investigations have also been carried out by the authorities to arrest every actor in acts of radicalism and terrorism, which resulted in a discovery that there were ; people out there dedicated their lives to being terrorists, recruiting potential terrorists, teaching terrorism, spreading understanding of Islamic religion that deviates, and convincing them to follow the teachings of Islamic religion in the style of terrorism. Radicalism and Terrorism in the global world, including Indonesia, have become one of very serious problems, because this phenomenon not only related to the home security but also global threat. The global waves of terrorism and radicalism have the international characteristic, borderless and transnational activity, even transnational organized crime. Therefore, this paper underlined and emphasized that combating international terrorism and radicalism cannot only be supported by one Country, but also it needed the international cooperation.